The Impact of Domestic Companies’ CSR Targets on Consumer Post-Purchase Responses: The Moderating Effects of Brand Reputation - Kikyoung Park (SAGE Open)
With the growing interest in the environment, society, and governance, responsible management emphasizes corporate social responsibility (CSR) activities. Drawing upon social identity theory, this study explores the interplay between a brand’s CSR target (domestic or abroad) and its reputation in shaping consumers’ post-purchase product attitudes. Through two complementary experiments, the findings reveal that consumers exhibit more favorable post-purchase attitudes toward domestic brands with a high reputation when their CSR activities are targeted domestically. Conversely, the target of CSR activities does not significantly impact post-purchase product attitudes toward domestic brands of lower reputation. Further analysis reveals that for high-reputation brands, the perceived fairness of CSR activities is crucial, whereas, for lower reputable brands, the role of CSR activities is essential in reducing product risk, making the target country of CSR irrelevant. This study indicates that CSR strategies should be customized according to brand reputation, with significant implications for enhancing sustainable consumer brand loyalty.